Epistemologi Hukum Islam Muslimah Hizbut Tahrir Indonesia (MHTI) dI Balik Gagasan Anti Kesetaraan Gender - Isnatin Ulfah (Justicia Islamica, 2013)
The struggle of feminists to liberate women from patriarchal domination and place them on equal footing with men is not shared by all women. Muslimah Hizbut Tahrir Indonesia (MHTI), a subordinate women's organization of HTI, rejected this effort. According to MHTI, women's natures, which are biologically different from men's, also carry implications for the differences in their respective roles;women at home taking care of children, men earning a living. For them, Islam has very clearly regulated these differences. MHTI's perception is inseparable from their perspective and understanding of religious doctrines and texts. In other words, religious fundamentalism turns out to be strongly influenced by the encouragement contained in the teachings of the religion itself. It is from this side that this paper is written, to find out their epistemological perspective in understanding religious texts.religious texts. It can simply be concluded that from an epistemological perspective, their rejection of gender equality turns out to be intertwined with their very textual understanding of the Qur'an and h} adi> th, and ignores the history of the text and the interpreter.